Nutritional status and toddler development: a relationship study - Nursyahid Siregar; Ratnawati Ratnawati; Rif'atul Amini (Jurnal Kesehatan Ibu dan Anak, 2020)
SDGs have an international target of 2025 for decreased stunting and wasting in infants. Stunting indicates that there is a manifestation of the problem of nutrient deficiency and infection experienced since or before the child's birth period in a long period that can affect the development of the brain, the maturity of muscle function becomes slow causing the motor ability to be obstructed. The purpose of this research is to analyze the relationship status of stunting and non-stunted nutrition with the development of toddlers in Mangkupalas community health center. This research is a descriptive-analytical study with a cross-sectional approach. Large samples were 82 toddlers taken with accidental sampling technique from July to October 2019 at Mangkupalas Public health center (PHC). Analyzed by testing hypotheses of research using Chi-square test with CI 95%. The results showed that there is 41 sample (50%) stunting, and 41 samples (50%) not stunting. Development status was 43 (52.4%) appropriate, 32 (39.0%) doubt, and 7 (8.5%) deviation. Chi-Square test result p-value= 0.000. There are relationships between stunting and non-stunting nutrition status to the development of toddlers.